The Effectiveness of E-Learning in Improving Student Motivation and Learning Outcomes - Anggita Dwi Nugroho; Nasuka Nasuka; Agus Raharjo (Journal of Physical Education and Sports, 2023)
Media is one of the factors that can influence student motivation and learning outcomes. The purpose of this study was to analyze the effectiveness of using e- learning media in improving student motivation and learning outcomes. The subjects in this study were VIII students of SMP N 3 Ajibarang. Data collection techniques used questionnaires and tests. Data analysis techniques using paired sample t test. The results showed a significant difference in scores before and after learning. The t test results showed a p value of 0.023 for learning motivation and p 0.001 for learning outcomes. These results indicate that the hypothesis is accepted that there is a significant difference in motivation and learning outcomes in the stages before and after learning.